Our place in the mental health world: An exploration of counsellors' professional identity - Antunes-Alves, Sara (University of Ottawa (Canada), 2010)
This study employed a variation of grounded theory method to investigate how seasoned counsellors in a midsized Canadian city experienced their counsellor professional identity. Six master's-level counsellors were interviewed using a semi-structured interview protocol to develop an understanding of how they define themselves as professionals, as well as how they view the counselling profession overall. Twenty-five themes emerged, which were further classified into five categories: (a) key influences on counsellor professional identity, which included seven themes; (b) counsellors' professional image, which included seven themes; (c) counsellors' roles and practices, which included six themes; (d) counsellor education and training, which included three themes; and (e) critical events of counsellor professional identity, which included two themes. Encouraging counsellors and counsellor trainees to reflect upon their professional identity and how it develops could foster a stronger professional identity among counsellors and ultimately promote a stronger and more unified image of the profession. Keywords: counselling, professional identity, counsellor education
Keywords: Education, Guidance and Counseling.